Market Day Activities as an Effort to Build the Character and Entrepreneurial Spirit of UPT SPF SD Inpres Mariso 2 Students - Arisah, Nur; Sirajuddin, Andi Muhlis; Wisudawaty, Ika (Cita konsultindo, 2024)
One of the qualities that is considered to show a person's ability and resilience in facing difficulties is his character and entrepreneurial spirit. People with an entrepreneurial spirit must be the ones who encourage nation building. The Market Day event is designed to foster creativity and growth for children while preparing the minds of business people and helping them understand the business world. It is hoped that this study will observe how market day activities help students develop their entrepreneurial spirit. This research was conducted at UPT SPF SD Inpres Mario 2 and used a qualitative methodology. Five students from the high grades, namely grades 4, 5 and 6 of the school, participated in the interview process. Data is collected by interviews and observations, and data coding methods are used for analysis. The results of this study aim to show that market day activities provide space for students to build their character and entrepreneurial spirit through direct buying and selling. Active participation of students in overcoming existing obstacles can encourage critical thinking, innovation and increase collaboration between students thereby stimulating the growth of their creativity.